Adhesion strength of tin coatings at various ion etching deposited on tool steels using cathodic ARC PVD technique - Ali, Mubarak L. (Elsevier, 2009)
Titanium nitride (TiN) widely used as hard coating material was coated on tool steels, namely on high-speed steel (HSS) D2 tool steel by physical vapor deposition method. The goal of this study was to examine the effect of ion etching with without titanium (Ti) chromium (Cr) on the adhesion strength of TiN coatings deposited on tool steels. From the scratch tester, it was observed that by increasing Ti ion etching showed an increase in adhesion strength of the deposited coatings. The coatings deposited with Cr ion etching showed poor adhesion compared with the coatings deposited with Ti ion etching. Scratch test measurements showed that the coating deposited with titanium ion etching for 16 min is the most stable coating maintained even at the critical load of 66 N. The curve obtained via penetration depth along the scratch trace is linear in the case of HSS, whereas is slightly flexible in the case of D2 tool steel. The coatings deposited on HSS exhibit better adhesion compared with those on D2 tool steel.